Mac saves the world - Barnett, Mac (Barnett, Mac. Mac B., kid spy, 2021)
Summoned by the Queen of England to save the world once again, trusty kid spy Mac B. navigates secret tunnels beneath the Berlin Wall to retrieve cheat codes from an adversarial scientist only to find himself trapped in East Germany.